2013
DOI: 10.1021/ef401908w
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Assessment and Surface Compositional Analysis of Aged Calcite Treated with Dynamic Water

Abstract: The following study investigates the effect of brine ionic composition and salinity (a mixture we call dynamic water) on calcite surface wettability alteration using atomic force microscopy (AFM) and surface compositional analysis using X-ray photoelectron spectroscopy (XPS) in addition to contact angle measurements. Three ions are particularly varied (Mg 2+ , Ca 2+ , and SO 4 2−) to examine their role for surface alteration. Dissolution, adsorption, and precipitation are among the processes competing at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…The effect was almost similar for the case of the aged dolomite as indicated by the plateau of zeta potential trends for the aged dolomite. In the study done by Abdallah and Gmira [43], it showed that the absorbability of Mg 2+ ions could be enhanced by the presence of Ca 2+ or SO 4 2− ions in the same solution. However, no strong conclusion can be made on such effect based on the obtained zeta potential due to the slight changes in zeta potential of the aged calcite and the aged dolomite as discussed here.…”
Section: Relative Effect Of the Potential Determining Ionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The effect was almost similar for the case of the aged dolomite as indicated by the plateau of zeta potential trends for the aged dolomite. In the study done by Abdallah and Gmira [43], it showed that the absorbability of Mg 2+ ions could be enhanced by the presence of Ca 2+ or SO 4 2− ions in the same solution. However, no strong conclusion can be made on such effect based on the obtained zeta potential due to the slight changes in zeta potential of the aged calcite and the aged dolomite as discussed here.…”
Section: Relative Effect Of the Potential Determining Ionsmentioning
confidence: 96%
“…Smith et al [42] also showed similar rhombohedral shapes caused by dissolution on a calcite chip immersed in NaCl brine. Very recently, Abdallah and Gmira [43] demonstrated a rapid development of rhombohedral structures on Iceland spar calcite chips immersed in deionized water and NaCl brine.…”
Section: Effect Of Ph and Adsorbed Carboxylic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low Salinity Waterflooding (LSW) is an enhanced oil recovery strategy that injects water, of a controlled ionic concentration and composition, into oil reservoirs [1][2][3], potentially yielding up to 40% extra hydrocarbon, depending on conditions and crude oil properties [1,4]. Even though LSW has been demonstrated as a promising approach to improve oil recovery factors, the principal mechanisms involved are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, water imbibition into pores is supported by the positive capillary pressure, which improves the oil recovery. It is widely accepted that carbonate rock formations are moderately to strongly oilwet [2,3]. This is attributed to the adsorption of polar compounds contained in crude oil such as carboxylic acids and asphaltenes, onto the carbonate surface, which results in the rock surface changing from hydrophilic to hydrophobic [2,4].…”
Section: Introductionmentioning
confidence: 99%